The impact of hydrogenation conditions on the temperature and strain discrimination of type i and type ia bragg grating sensors - Kalli, Kyriacos; Simpson, Alexander George; Zhou, Kaiming (My University, 2006)
We report experimental findings for tailoring the temperature and strain coefficients of Type I and Type IA fibre Bragg gratings by influencing the photosensitivity presensitisation of the host optical fibre. It is shown that by controlling the level of hydrogen saturation, via hot and cold hydrogenation, it is possible to produce gratings with lower thermal coefficients. Furthermore, there is a larger difference between the Type I and Type IA thermal coefficients and a significant improvement in the matrix condition number, which impacts the ability to recover accurate temperature and strain data using the Type1-1A dual grating sensor.
Keywords: Bragg gratings; Optical fibers; Hydrogenation